Effect of Confinement by COVID-19 on the Lifestyle of the University Population of Argentina: Evaluation of Physical Activity, Food and Sleep (Efecto del confinamiento por COVID-19 sobre el estilo de vida en población universitaria de Argentina: Evaluaci - Leonardo Intelangelo; Nacim Molina Gutiérrez; Nicolás Bevacqua; Cristian Mendoza; Iris Paola Guzmán-Guzmán; Daniel Jerez-Mayorga (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2022)
Objective: to determine lifestyle changes, such as physical activity, nutrition, and sleep in an Argentinean university population, caused by confinement during the COVID-19 pandemic. Methods: Cross-sectional study via web survey. 1021 the Argentinean university population (women, n = 645 and men, n = 376) aged between 18–70 years old was participate. Survey was utilized to measure participant physical activity behavior, nutrition, and sleep April to May 2020. Results: the main findings revealed that 4.3% of the sample showed obesity; the highest proportion of the sample stayed more than 6 hours in a sedentary status; 21.74% reported bad sleep quality; a reduction in good feeding pattern; and an increase in subjects who do not perform physical activity. According to socio-demographic and anthropometric factors, being a student (OR 2.19, CI95% 1.18 - 4, p= .012), overweight (OR 1.71, CI95% 1.19 – 2.44, p= .003), obesity (OR 4.45, CI95% 2.27 – 8.7, p< .001), and have been confined more than 45 days was associated with bad feeding. Likewise, low physical activity levels were associated with obesity (OR 3.2 CI95% 1.66 – 6.18, p= .001), being female (OR 1.61, CI95% 1.14 –2.28, p= .006) and get married (OR 1.72, CI95% 1.14 – 2.61, p= .009). Moreover, being a student was associated with poor sleep quality (OR 43.6, CI95%5.4 – 350, p< .001). Conclusion: This study suggests that confinement decreased healthy living habits such as good nutrition and physical activity and affected the quality of sleep in young subjects.